Economic development in the Carpathian basin in the light of population trends in Vojvodina - Juhász, Bálint (Studia Mundi – Economica, 2021)
Vojvodina, a geographical and administrative unit, is located in the northern part of Serbia and has a favorable geographical location. The area was characterized by intensive population movements and constant changes in national proportions. Today, 26 nationalities live in its territory, of which the Hungarian minority community is the most significant. There are six official languages in use in the provincial offices. The indisputable preconditions for the preservation of national identity: the possibility of using the mother tongue, organizing mother tongue education, providing information in the mother tongue and living and passing on folk traditions and culture to new generations. At the same time, everyday living issues also significantly affect the chances of staying in the homeland and preserving national identity. In 2016, in order to preserve the foreign parts of the community, the Government of Hungary launched the Carpathian Basin Economic Development Program, in the framework of which about HUF 300 billion worth of development has been realized so far, with about HUF 158.4 billion worth of support thousands of jobs were created besides Vojvodina, in Transcarpathia, Transylvania, Felvidék, Muravidék and Drávaszög. The research focuses on the correlations between population processes and economic development programs, relying primarily on the results of Vojvodina and other cross-border economic development programs, as well as on official census data.